Administração judiciária e os juizados especiais cíveis: o caso do Rio Grande do Sul - Schmidt, Ricardo Pippi (2008)
The Special Courts has been created to promote access to Justice, by a simple and quickly form, without fees, with the purpose of resolving issues of small complexity, on an informal way, and preferently in a consensual basis. Even though the system is on operation for the past two decades in Rio Grande do Sul, neither the Judiciary High Administration nor his operators have been giving it the proper attention. The contamination risk of traditional justice system practices, more bureaucratic and formalist - and because of this, slow -, requires some measures to avoid distortion of the principles upon which this Special Court has been conceived. The correct performance of the Presiding Judges and of the Special Court’s staff, the previous preparation of the 'Lay-Judges' and 'Conciliators' to the exercise of their important functions, the commitment of the Appeal Court’s components with the system unity and, specially, it’s management by a central department responsible for the Special Courts coordination and supervision are measures that, besides the proper investments in information technology, innovation incentives and the use of new technologies, procedures standardization, database improvement and statistic system, may promote significant improvements on its performance.